Word Familiarity and Lexical Change : The Case of Sarawak Malay Dialect - Radina, Mohamad Deli; Rosnah, Mustafa; Monaliza, Sarbini-Zin (Centre for Language Studies, 2012)
This preliminary study looks at the familiarity rating of words in Sarawak Malay Dialect (SMD). Although familiarity ratings of language items are usually utilised in psycholinguistic research, they can be very useful for studies in the area of language change. The aim of this study is twofold: (1) to compare the perceptive familiarity rating of Sarawak Malay words; and (2) to document Sarawak Malay words that are undergoing lexical change. Fifty SMD words were used in this study consisting of those with meanings that can be considered as medium to high in frequency for everyday speech. Questionnaires were designed using a 5- point Likert-type scale to rate word familiarity and distributed to 15 participants who were native SMD speakers between the ages of 20 and 25. Across word items, more than one third were found to be rated as less familiar and unknown and thus were not actively used in daily conversations. There were also a number of words perceived as familiar to highly familiar but were not widely used in everyday speech. Evidently, it is crucial to document and preserve these SMD words as they are fast becoming passive vocabulary for the young and may eventually be lost in their lexicon.